Intranasal pressure splints - a reliable alternative to nasal packing in septal sur (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To compare the outcome of nasal packing and intranasal pressure splints in patients undergoing septoplasty. Study design: Randomized controlled trial.Place and Duration of Study: The study was carried out at otorhinolaryngology department of  Combined Military Hospitals, Bahawalpur and Murree from June 2010 to November 2011.Methods: A total of 160 patients aged 15 to 50 years, undergoing septoplasty, were included  in the study and distributed in two equal groups. Group A with nasal packing, was compared with group B in which nasal splints were placed and no nasal packing was done. Post operative  morbidity in terms of pain, headache, epiphora, dysphagia and sleep disturbance along with post operative complications including nasal bleed, septal hematoma and synechiae formation were assessed over a follow up period of four weeks.Results: Patients in which nasal packing was done had significantly more post operative pain (p < 0.05) and a significantly higher incidence of headache, epiphora, dysphagia and sleep disturbance on the night of surgery (p < 0.05). There was no significant difference between two groups with respect to nasal bleeding, septal hematoma and synechiae formation.Conclusion: Pressure splints around nasal septum are effective alternative to nasal packing. With the use of these splints, nasal packing can be easily avoided following septal surgery, thus minimizing post operative discomfort of the patient. DOI: http://dx.doi.org/10.3329/bjo.v18i2.11985 Bangladesh J Otorhinolaryngol 2012; 18(2): 124-128